Sooting tendency analysis of oxygenate-diesel blended fuels by the affecting indicators of carbon number, oxygen content and H/C ratio. (15th April 2021) - Fang, Jun; Liu, Ying; Wang, Kun; Shah, Hassan Raza; Mu, Shanjun; Lang, Xuqing; Wang, Jingwu
Highlights: New affecting indicators along with an algorithm were introduced. The indicators are affecting oxygen content, carbon number and H/C ratio. Relative Weight gives the priority order of the three affecting indicators. Affecting indicators with RWs can interpret the sooting tendency of blends. Abstract: This study experimentally assessed the sooting tendencies of the diesel fuel blended with typical oxygenated additives. Based on the known influential factors of oxygenated functional group, oxygen content, carbon number, and saturation degree, the functional numbers of carbon and oxygen atoms of the molecules were determined by considering the actual bonding ratio of carbon and oxygen producing CO and CO2 during the combustion of blends. The affecting indicators along with a calculation algorithm were proposed, taking into account the actual effect of each factor on sooting tendency. So-called indicators were termed the affecting oxygen content, carbon number and H/C ratio. Normalized Oxygen Extended Sooting Index (OESI) values incorporating the smoke point values were established to decrease with increasing blending percentage of the oxygenated additives in blends, following an exponential fitting relationship. The resulting exponents quantified the soot inhibition ability of the oxygenated additives, which decreased in the order: ethanol (EA) > n-butanol (NBA) > methyl tertiary-butyl ether (MTBE) > dimethoxy methane (DMM) > methyl decanoate (MD) > methyl butanoate (MB) > dibutyl maleate (DBM) > dimethyl carbonate (DMC). A combination of the absolute affecting indicator values generated by the suggested algorithm and their relative weights obtained by Relative Weight Analysis (RWA) could interpret the sooting tendency of most of the blended fuels very well. It was found that the sooting tendency was mainly determined by the absolute values of the affecting indicators, and the priority should follow the results by RWA, that decreased in the order of affecting carbon number > affecting oxygen content > affecting H/C ratio. This study could benefit the evaluation of the sooting tendency of the oxygenate-diesel blended fuels.